Employability, organizational commitment and person–organization fit among nurses in China: A correctional cross‐sectional research. Issue 1 (3rd August 2022) - Yan, Wei; Wu, Xingqu; Wang, Huan; Zhang, Yaling; Cheng, Lixia; Zhou, Xinyao; Chen, Huan; Song, Caiping; Ye, Junying
Abstract: Aim: This study aimed to explore the effect of training on organizational commitment, the mediating effect of employability and the moderating role of person–organization fit. Design: A correctional cross‐sectional research design was adopted for this study. Methods: A questionnaire‐based survey of 859 nurses in a public hospital in Western China was conducted to identify their perceptions of training, employability, organizational commitment and person–organization fit. Hierarchical linear regression and conditional process analysis on moderated mediation were performed. Results: Training had a positive effect on organizational commitment ( p < .01). Internal and external employability mediated the relationship between training and organizational commitment ( p < .01). Person–organization fit enhanced the indirect effect of training on organizational commitment through external employability ( p < .05).